PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN STRATEGI BELAJAR AKTIF QUESTIONS STUDENTS HAVE DENGAN PEMBELAJARAN KONVENSIONAL SISWA KELAS VIII SMP NEGERI 7 MERANGIN - Mira Yani; Muhammad Jainuri (Mat-Edukasia, 2017)
This study aims to describe the mathematical problem solving abilities using the Questions Student Have strategy better than conventional learning of class VIII students of SMP 7 Merangin 2015/2016 Academic Year. This study uses a quantitative approach to the experimental method with a population of eighth grade students of SMP N 7 Merangin in the 2015/2016 Academic Year totaling 74 people. The sampling technique uses Simple Random Sampling. The selected sample is class VIII A as the experimental class and VIII C as the control class. Data collection techniques through tests of mathematical problem solving abilities in the form of essay questions with the number of five items in the cube and beam material given in class VIII B. The data analysis technique used to test the hypothesis is the t-test. From the analysis of final test data in the experimental class obtained an average score of 51.17, variance of 7.281, while the control class obtained an average score of 46.52, variance of 10.108. Hypothesis test results obtained, tcount = 1.84 and ttable = 1.68. Or 1.84> 1.68 this means tcount > ttable so Ho is rejected and Ha is accepted. The conclusion of this study is that mathematical problem solving abilities using the Questions Student Have strategy are better than using conventional learning by class VIII SMP N 7 Merangin 2015/2016 Academic Year. Keywords: Strategies for Student Student Questions, Mathematical Problem Solving Capabilities